2003
DOI: 10.1111/1469-7610.t01-1-00139
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and the development of conduct disorder and hyperactive symptoms in childhood: a prospective longitudinal study from 2 months to 8 years

Abstract: These data would suggest that only in boys was there evidence for the existence of a sensitive period for the development of hyperactive symptoms, and to a lesser extent, conduct disorder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 137 publications
(132 reference statements)
8
113
1
3
Order By: Relevance
“…Cut point = top 20th percentile. Mother's depressive symptoms · Twelve-item measure adapted from Center for Epidemiological Studies Depression scale 61 to capture presence and severity of depression symptoms in the past week. Theoretical range 0 to 36; higher score indicates more depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cut point = top 20th percentile. Mother's depressive symptoms · Twelve-item measure adapted from Center for Epidemiological Studies Depression scale 61 to capture presence and severity of depression symptoms in the past week. Theoretical range 0 to 36; higher score indicates more depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…61 Emotional dysregulation at 9 months of age was associated with development of conduct disorder at age 5 and 8 years. 61 From the perspective of cognitive social theory, young children exposed to negative parenting may model the negative cognitions and aggression of their mothers. 62 Analyses from this study do not explain whether the effects of hostile/ineffective parenting on aggression are direct through observational learning, indirect through a negative emotional environment, or a combination of both.…”
Section: Discussionmentioning
confidence: 96%
“…Difficulties in attunement between parent and child can have profound effects on aspects of cognitive and social functioning including stress responses and language development (Schore 1997;Trevarthen 2001). Research on post-natal depression has shown that children of depressed mothers may have lasting cognitive difficulties (Murray & Cooper 1997) and behavioural problems (Morrell & Murray 2003), and these are likely to be a consequence of difficulties in the early parent-child relationship. Harsh parenting is known to interact with child temperament in increasing risk for conduct disorder (Scaramella & Leve 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While the role of the breastfeeding in the brain develop- ment still remains unclear, it is possible that the some cognitive or behavioural dysfunction may be the result of the short duration of breastfeeding [30]. Other longitudinal studies have confirmed that interactions between biological vulnerability and poor parenting are important in predicting further externalising problems [5,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%